The Effectiveness of Contextual Learning Approach in Improving Civic Education Learning Outcomes - Moh Thohir; Alfan Bramantya; Eko Pujiati; Dian Utami Ikhwaningrum (Bulletin of Pedagogical Research, 2026)
Vocational education in Vocational High Schools requires learning that is not only oriented to mastering concepts, but also to students' ability to apply knowledge contextually following the demands of the contextual problem. However, the dominance of conventional learning still has the potential to produce learning outcomes that are less meaningful and difficult to transfer to real situations. Therefore, this study aims to analyze the effectiveness of the contextual learning approach in improving the learning outcomes of vocational school students. A quantitative research methodology was applied using a quasi-experimental pretest–posttest control group design to examine the effects of the intervention. The research population was class X students at SMK Darul Amin Madura, with a sample of 80 students divided into experimental groups and control groups of 40 students each. The results revealed a statistically significant difference in posttest scores, with the experimental group outperforming the control group with t score equivalent to 3.27 (p < 0.01). ANCOVA results confirmed that the learning approach had a significant effect on learning outcomes after controlling for initial ability (F = 10.84; p < 0.01; partial η² = 0.12). In addition, the N-gain value of the experimental group (M = 0.67; moderate–high category) was higher than that of the control group (M = 0.38; moderate category). These findings show that the contextual learning approach is effective in improving the learning outcomes of vocational school students.